Nilai Perusahaan Dan Faktor Yang Mempengaruhinya - Kodriyah Muhaimin; Lutfyana Hanifah (Jurnal Akuntansi Manajemen (JAKMEN), 2023)
This study aims to examine and analyze the significant effect of Tax Planning, Intellectual Capital and Independent Commissioners on Firm Value (Empirical Study on Banking Companies listed on the Indonesia Stock Exchange for the 2017-2021 Period). This research uses purposive sampling method. The population in this study were 47 companies and obtained a sample of 35 companies with a total of 175 company data, after processing the data there were 87 data outliers. The total sample used in this study was 88 company data. The data analysis method used is multiple linear regression analysis and the data is processed using SPSS version 26. The results of this study indicate that 1) Tax Planning has a significant effect on Firm Value, 2) Intellectual Capital has no significant effect on Firm Value, 3) Commissioner Independent has a significant effect on firm value.